Worldwide Chronic Retrieval Experience of Helix-Fixation Leadless Cardiac Pacemakers - Neuzil, Petr; Exner, Derek V; Knops, Reinoud E; Cantillon, Daniel J; Defaye, Pascal; Banker, Rajesh; Friedman, Paul; Hubbard, Chris; Delgado, Stephanie M; Bulusu, Anuradha; Reddy, Vivek Y (Journal of the American College of Cardiology, 2025)
The growing use of leadless pacemaker (LP) technology requires safe and effective solutions for retrieving and removing these devices over the long term. This study sought to evaluate retrieval and removal of an active helix-fixation LP studied in worldwide regulatory clinical trials. Subjects enrolled in the LEADLESS II phase 1 investigational device exemption, LEADLESS Observational, or LEADLESS Japan trials with an attempted LP retrieval at least 6 weeks postimplantation were included. The retrieval success rate was evaluated for all attempted retrievals. Site-reported complications associated with LP retrievals were quantified, with the severity and relationship adjudicated by an independent clinical events committee. There were 1,423 successful LP implants and 234 chronic LP retrieval attempts in 233 subjects. The overall retrieval success rate was 87.6% (205 of 234 attempts). The most common reason for failed retrieval (86.2%, 25 of 29 attempts) was inability to access the LP docking button. The mean time from implantation to attempted retrieval was 3.2 years (range 0.2-9.0 years) and did not significantly influence the retrieval success (P = 0.71). The clinical events committee adjudicated 11 complications in 9 subjects as being retrieval related (3.9%, 9 of 233 subjects). The safety and efficacy of chronic LP retrieval of an active helix-fixation device was demonstrated in an international clinical trial setting, with implant durations up to 9 years.